Hybrids of plants and of ghosts - Graham, Jorie, 1950- (Princeton series of contemporary poets, 1980)
"How I would like to catch the world / at pure idea," writes Jorie Graham, for whom a bird may be an alphabet, and flight an arc. Whatever the occasion--and her work offers a rich profusion of them--the poems reach to where possession is not within us, where new names are needed and meaning enlarged. Hence, what she sees reminds her of what is missing, and what she knows suggests what she cannot. From any event, she arcs bravely into the farthest reaches of mind. Fast readers will have trouble, but so what. To the good reader afraid of complexity, I would offer the clear trust that must bond u.